A Planar 4-Bit Reconfigurable Antenna Array Based on the Design Philosophy of Information Metasurfaces. (October 2022) - Wang, Zheng Xing; Yang, Hanqing; Shao, Ruiwen; Wu, Jun Wei; Liu, Guobiao; Zhai, Feng; Cheng, Qiang; Cui, Tie Jun
Abstract: Inspired by the design philosophy of information metasurfaces based on the digital coding concept, a planar 4-bit reconfigurable antenna array with low profile of 0.15 λ 0 (where λ 0 is the free-space wavelength) is presented. The array is based on a digital coding radiation element consisting of a 1-bit magnetoelectric (ME) dipole and a miniaturized reflection-type phase shifter (RTPS). The proposed 1-bit ME dipole can provide two digital states of "0" and "1" (with 0° and 180° phase responses) over a wide frequency band by individually exciting its two symmetrical feeding ports. The designed RTPS is able to realize a relative phase shift of 173°. By digitally quantizing its phase in the range of 157.5°, additional eight digital states at intervals of 22.5° are obtained. To achieve low sidelobe levels, a 1:16 power divider based on the Taylor line source method is employed to feed the array. A prototype of the proposed 4-bit antenna array has been fabricated and tested, and the experimental results are in good agreement with the simulations. Scanning beams within a ±45° range were measured with a maximum realized gain of 13.4 dBi at 12 GHz. The sidelobe and cross-polarization levels are below –14.3 and –23.0 dB, respectively. Furthermore, the beam pointing error is within 0.8°, and the 3 dB gain bandwidth of the broadside beam is 25%. Due to its outstanding performance, the array holds potential for significant applications in radar and wireless communication systems.